Challenges and hope: latest research trends in the clinical treatment and prognosis of liposarcoma - Hongliang Liu; Xi Wang; Xiaoyu Wang; Fabo Qiu; Bin Zhou (Frontiers in Pharmacology)
Liposarcoma, as a complex disease, is characterized by intricate interactions between distinct histopathological subtypes and corresponding clinical outcomes, emphasizing the necessity of personalized approaches in diagnosis and treatment strategies. This malignant tumor originating from adipose tissue is classified into different subtypes with specific molecular markers, which not only distinguish them but also guide treatment directions. The main approach for treating liposarcoma is surgical resection, with the aim of complete excision and achieving clean margins (R0 resection) to minimize the risk of recurrence. This surgical principle emphasizes the critical need for precise preoperative planning, and in certain cases, the integration of neoadjuvant therapy may be needed to reduce the tumor to a surgically manageable size. In addition to surgery, systemic therapy plays a key role in the advanced stages of the disease, especially when resistance to traditional treatment arises. The emergence of novel systemic therapies, including chemotherapy, targeted therapy, and immunotherapy, has opened new avenues for treating this challenging malignancy. These systemic therapies are selected on the basis of the specific molecular features of the tumor, highlighting the importance of detailed molecular diagnostics. As our understanding of the molecular basis of liposarcoma deepens, integrating clinical and molecular features is crucial for optimizing treatment outcomes. This comprehensive approach, which combines surgical precision with systemic therapy innovations, will change the treatment landscape for patients with liposarcoma, advancing toward more personalized and effective treatment strategies.